Repetitive prefrontal tDCS activates VTA dopaminergic neurons, resulting in attenuation of Alzheimer’s Disease-like deficits in Tg2576 mice - Maria Luisa De Paolis; Gilda Loffredo; Paraskevi Krashia; Livia La Barbera; Annalisa Nobili; Emma Cauzzi; Lucy Babicola; Matteo Di Segni; Roberto Coccurello; Stefano Puglisi-Allegra; Emanuele Claudio Latagliata; Marcello D’Amelio (Alzheimer’s Research & Therapy)
Abstract Background Emerging evidence implicates early dysfunction of dopaminergic neurons in the Ventral Tegmental Area (VTA) as a key contributor to Alzheimer’s Disease (AD) pathophysiology. Specifically, the VTA dopaminergic neurodegeneration and the consequent reduction of dopamine (DA) in mesocorticolimbic targets are associated with the onset of cognitive impairments and neuropsychiatric-like manifestations in AD animal models. Moreover, decreased midbrain volume and functional VTA disconnection are identified as predictors of accelerated progression from Mild Cognitive Impairment to AD-dementia in clinical populations. Given these findings, interventions capable of directly modulating VTA activity and augmenting DA release, despite the ongoing neurodegeneration, may hold therapeutic potential for mitigating DA-related deficits in AD. This study aims at evaluating the therapeutic potential of prefrontal transcranial Direct Current Stimulation (tDCS) in the Tg2576 mouse model of AD, exhibiting early VTA dopaminergic neurodegeneration. Methods Repeated tDCS was applied to assess its ability to activate VTA DA neurons. We also evaluated tDCS effects on synaptic plasticity, cognitive and non-cognitive behaviours and AD-related pathology. Hippocampal DA release and Nucleus Accumbens (NAc) DA transporter (DAT) expression were measured. With immunohistochemistry we examined microglial density and morphological complexity at different disease stages. Additionally, intracellular amyloid-β (Aβ) levels and plaque burden were evaluated to determine the impact of tDCS on AD pathology. Results Prefrontal tDCS enhanced the activity of VTA dopaminergic neurons, leading to increased hippocampal DA release and higher DAT levels in the NAc. The enhanced DA outflow is associated with restored CA3-CA1 synaptic plasticity and improvements in recognition memory and motivational behaviours. tDCS reduced microglial numbers and morphological complexity in Tg2576 mice at both pre-plaque stage (7-months) and at an advanced stage characterized by plaque accumulation (12-months). Notably, tDCS also decreased Aβ plaque burden, although no changes in intracellular Aβ levels were observed in younger Tg2576 mice. Conclusions These findings highlight the multifaceted therapeutic potential of prefrontal tDCS in targeting key AD pathophysiological hallmarks, including dopaminergic dysfunction, synaptic impairments, neuroinflammation and plaque deposition. As a non-invasive neuromodulatory approach, prefrontal tDCS emerges as a promising early intervention strategy to complement existing AD treatments, with the potential to improve patient outcomes and quality of life.